2015
DOI: 10.21275/v4i12.nov151817
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Concept Mapping Strategy on Achievement in Chemistry of IX Graders in Relation To Gender

Abstract: Abstract:The study was carried out to investigate the effect of teaching through Concept mapping on the achievement in Chemistry in relation to gender. Sample of the study consisted of 236 (118 experimental group and 118 controlled group) IX class students from four Government schools of Ludhiana city. Experimental group was exposed to Concept mapping method and the controlled group was exposed to Conventional method (lecture and discussion). Mixed group intelligence test (MGTI) by Mehrotra (2008) was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Soltani et al (2012), Demirkol (2014), Ceylan andKesici (2017), andAl Bataineh et al (2019) all confirmed that blended learning is superior to traditional learning. Similarly, Ghazizadeh and Fatemipour (2017), Oweis (2018), Hijazi and AlNatour (2020), Sharma and Sharma (2020) confirmed the current results. Recent studies from 2022, such as Apsari and Parmawati (2022), Fardin et al (2022), Mohamed (2022), andMiraei Mohammadi et al (2022), all validated the findings where statistically significant differences existed favouring blended learning over traditional face-to-face learning.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Soltani et al (2012), Demirkol (2014), Ceylan andKesici (2017), andAl Bataineh et al (2019) all confirmed that blended learning is superior to traditional learning. Similarly, Ghazizadeh and Fatemipour (2017), Oweis (2018), Hijazi and AlNatour (2020), Sharma and Sharma (2020) confirmed the current results. Recent studies from 2022, such as Apsari and Parmawati (2022), Fardin et al (2022), Mohamed (2022), andMiraei Mohammadi et al (2022), all validated the findings where statistically significant differences existed favouring blended learning over traditional face-to-face learning.…”
supporting
confidence: 89%
“…International Journal of Instruction, April 2023 • Vol.16, No.2 Traditional or face-to-face learning environments have been chastised for promoting passive learning, failing to address higher-order thinking skills, and failing to account for individual differences and needs (Sharma & Sharma, 2020, Magableh & Abdullah, 2021. Face-to-face instruction and feedback are combined with online instructions and feedback in blended learning.…”
Section: The Effect Of Blended Learning On the Primary Stage Efl …mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the results showed that the concept map learning strategies are more effective (Chawla, 2015;Tarkashvand, 2015;Chiou et al, 2017). Other research results also showed that the concept map learning strategies are better than the conventional learning strategy in increasing attitudes towards science (Karakuyu, 2010), learning motivation (Hwang, Which is More Effective, a Mind Map or a Concept Map ... Shi, & Chu, 2011), critical thinking skills (Lestari, Saryantono, Syazali, Saregar, Madiyo, Jauhariyah, & Umam, 2019), and learning interest (Lestari et al, 2019).…”
Section: Which Is More Effective a Mind Map Or A Concept Map Learning Strategy?mentioning
confidence: 98%
“…More so, concept mapping attracts student's attention, motivates them, facilitates recall of information and hence, enhances their achievement. Jaya (2015) asserted that to be successful in learning; students have to take the passion of knowledge actively by seeking expert conceptual linkages between new concepts and those they already possess. Concept learning breaks down the task to be learned into smaller units.…”
Section: Discussionmentioning
confidence: 99%